Karakteristik Kepemimpinan Pembelajaran Era Digital dan Pemecahan Masalah Pembelajaran Masa Pandemi Covid 19 - Djum Djum Noor Benty; Mustiningsih Mustiningsih; Anindya Hapsari (Universitas Negeri Malang, 2022)
Abstract: This Covid-19 pandemic situation makes school principals play an important role in solving problems related to learning problems during the covid 19 pandemic. The purpose of this study is to identify the characteristics of digital era instructional leadership and solving learning problems during the covid 19 pandemic. This study uses a research design descriptive quantitative. Area proportional random sampling is a sampling technique used, with a total sample of 196 people. The results of the study show (1) that instructional leadership skills in the digital era are the most needed factors for building a school climate, which are then followed by exemplary factors, strengthening, learning in the classroom and outside the classroom, preparing the vision, mission, and school goals that contain era learning digital, and learning program management, and (2) the principal's skills in solving learning problems during the Covid 19 pandemic are the most needed decision implementation skills factors, which are then followed by problem identification, evaluation, alternative development, and analysis skills factors. decide on alternatives.Keywords: instructional leadership, problem solving, digital era, covid 19 Abstrak: Situasi pandemi Covid-19 ini menjadikan Kepala sekolah memegang peranan penting dalam pemecahan masalah terkait dengan permasalahan pembelajaran di masa pandemi covid 19. Tujuan penelitian ini yakni untuk mengidentifikasi karakteristik kepemimpinan pembelajaran era digital dan pemecahan masalah pembelajaran masa pandemi covid 19. Penelitian ini menggunakan rancangan penelitian kuantitatif deskriptif. Area proportional random sampling merupakan teknik pengambilan sampel yang digunakan, dengan jumlah sampel sebanyak 196 orang. Hasil penelitian menunjukkan (1) keterampilan kepemimpinan pembelajaran era digital paling banyak dibutuhkan faktor membangun iklim sekolah, yang selanjutnya secara berturut-turut diikuti faktor keteladanan, penguatan, belajar di kelas dan diluar kelas, penyusunan visi, misi, dan tujuan sekolah yang berisi pembelajaran era digital, dan pengelolaan program belajar, dan (2) keterampilan kepala sekolah dalam pemecahan masalah pembelajaran masa pandemi Covid 19 paling banyak dibutuhkan faktor keterampilan implemetasi keputusan, yang selanjutnya secara berturut-turut diikuti faktor keterampilan identifikasi masalah, evaluasi, pengembangan alternatif, dan analisis dan memutuskan alternatif.Kata kunci: kepemimpinan pembelajaran, pemecahan masalah, era digital, covid 19